Investigations of an increased incidence of non-Aspergillus invasive mould infections in an onco-haematology unit (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: Invasive mould infections are life-threatening complications in patients with haematologic cancer and chemotherapy-induced neutropenia. While invasive aspergillosis represents the main cause of invasive mould infections, non-Aspergillus mould infections, such as mucormycosis, are increasingly reported. Consequently, their local epidemiology should be closely monitored. The aim of this study was to investigate the causes of an increased incidence of non-Aspergillus mould infections in the onco-haematology unit of a Swiss tertiary care hospital.METHODS: All cases of proven and probable invasive mould infections were retrospectively identified via a local registry for the period 2007–2021 and their incidence was calculated per 10,000 patient-days per year. The relative proportion of invasive aspergillosis and non-Aspergillus mould infections was assessed. Factors that may affect invasive mould infections’ incidence, such as antifungal drug consumption, environmental contamination and changes in diagnostic approaches, were investigated.RESULTS: A significant increase of the incidence of non-Aspergillus mould infections (mainly mucormycosis) was observed from 2017 onwards (Mann and Kendall test p = 0.0053), peaking in 2020 (8.62 episodes per 10,000 patient-days). The incidence of invasive aspergillosis remained stable across the period of observation. The proportion of non-Aspergillus mould infections increased significantly from 2017 (33% vs 16.8% for the periods 2017–2021 and 2007–2016, respectively, p = 0.02). Building projects on the hospital site were identified as possible contributors of this increase in non-Aspergillus mould infections. However, novel diagnostic procedures may have improved their detection.CONCLUSIONS: We report a significant increase in non-Aspergillus mould infections, and mainly in mucormycosis infections, since 2017. There seems to be a multifactorial origin to this increase. Epidemiological trends of invasive mould infections should be carefully monitored in onco-haematology units in order to implement potential corrective measures.